Transmettrelecinema.com : une plateforme pédagogique pour une certaine transmission d’un certain cinéma - Barbara Laborde (Communiquer)
This article proposes a semiological analysis of the discourses and the editorialization of the educational videos available on the official platform of the CNC “Transmettre le cinéma”. It is observed the audiovisual staging of the videos, the analysis of the lexical content of the speeches, and the functionalities of the platform. In the opinion of teachers and mediators who use this pedagogical tool and the protagonists who express themselves on this platform seem more or less linked by common representations. Unsurprisingly, there emerged a certain anchoring of modern cinephilia as it has been deployed in France since the 1960s, there is also a disjunction between cinephilic discourse and educational expectations, testifying to tensions (including economic ones) within the institution itself. The analysis shows that the CNC, through this online platform, is trying to reconfigure itself in the current communicational and pedagogical paradigms between plebiscite and mistrust of the Internet and the new cinephilies expressed there.